2006
DOI: 10.1103/physrevd.74.094012
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Form of the Isgur-Wise function in the BPS limit

Abstract: Using previously formulated sum rules in the heavy quark limit of QCD, we demonstrate that if the slope 2 ÿ 0 1 of the Isgur-Wise (IW) function w attains its lower bound 3 4 , then all the derivatives ÿ1 L L 1 attain their lower bounds 2L1!! 2L, obtained by Le Yaouanc et al. This implies that the IW function is completely determined, given by the function w 2 w1 3=2 . Since the so-called BPS condition proposed by Uraltsev implies 2 3 4 , it implies also that the IW function is given by the preceding expression. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…(19,20). On the quantitative level it is not a priori clear, at which scale µ these sum rules are saturated and by which kind of states.…”
Section: The Ope Treatmentmentioning
confidence: 99%
“…(19,20). On the quantitative level it is not a priori clear, at which scale µ these sum rules are saturated and by which kind of states.…”
Section: The Ope Treatmentmentioning
confidence: 99%
“…In what follows there is some unavoidable overlap with our Appendix B of ref. [13] from which some points are worth to be recalled.…”
Section: Introductionmentioning
confidence: 99%
“…the subindex 0 denoting the value of w for q 2 = m It is interesting to notice that the rates (12), (13) are given, assuming the D * * for a given j = to be degenerate, by the expressions…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated [10], using the above SR, that if the slope reaches its lower bound (1), as happens in the BPS limit, then all derivatives reach their lower bounds (2), and then the Isgur-Wise function is completely fixed, namely…”
mentioning
confidence: 99%
“…Using the formalism of Leibovich et al [13], we have demonstrated in [10], using translational invariance, the equations of motion and the BPS condition (15) that the slope and the curvature of the IW function satisfy :…”
mentioning
confidence: 99%